Predicting Academic Help-Seeking Intentions Using the Reasoned Action Model - Thomas, Christopher L.; Tagler, Michael J. (Frontiers in Education, 2019)
Seeking help when confronted with academic difficulties is an adaptive self-regulated learning strategy that facilitates positive academic outcomes. However, many students are reluctant to seek help with academic difficulties. The current study used the Reasoned Action Model to investigate the determinants of students’ intentions to utilize university-based sources of academic support. Participants (N = 125) in Study 1 responded to open-ended questions designed to identify salient behavioral, normative, and control beliefs contributing to the use of university-based academic support services. Participants (N = 176) in Study 2 completed measures to assess attitudes, perceived normative pressure, perceived behavioral control, and behavioral intentions. Normative pressure was the strongest predictor of intentions to use university-based academic support, followed by attitudes. These results suggest that interventions targeting normative and behavioral beliefs may be effective in increasing academic help-seeking.